Synergistic effects of PS-NPs and Cd on ovarian toxicity in adolescent rats: Ferroptosis by induction of mitochondrial redox imbalance via the SIRT3-SOD2/Gpx4 pathway - Hua Wu; Lihua Feng; Huang Wu; Lihong Wang; Hengyi Xu; Fen Fu (Ecotoxicology and Environmental Safety)
Nanoplastics (NPs) are an emerging class of pollutants. They can act as a“Trojan horse” to change the bioavailability and toxicity of heavy metals in the environment. However, research on the combined toxicity of heavy metals and NPs is scarce, especially during the critical developmental period of adolescence. In this study, polystyrene nanoplastics (PS-NPs) and/or cadmium (Cd) were exposed to 4-week-old female rats for 28 days, with the aim of exploring the potential effects of combined exposure to PS-NPs and Cd on the ovaries of adolescence rats. Results showed that co-exposure to PS-NPs and Cd exacerbated ovarian toxicity in rats, primarily through increased atretic follicle numbers and endocrine disruption. Further studies revealed that PS-NPs and Cd synergistically repressed the SIRT3-SOD2/Gpx4 pathway, inducing mitochondrial oxidative stress and ferroptosis, resulting in damage to ovarian structure and function. However, the addition of the mitochondrion-targeted antioxidant SS-31 and the ferroptosis inhibitor Fer-1 reversed the harm to the ovaries from co-exposure to PS-NPs and Cd, the aberrant expression of genes related to the SIRT3-SOD2/Gpx4 pathway was also improved. Our results suggested that co-exposure to PS-NPs and Cd may trigger ferroptosis by inhibiting the SIRT3-SOD2/Gpx4 pathway, leading to mitochondrial redox imbalance, which provided novel insights into reproductive toxicity due to the interaction of PS-NPs and Cd during adolescence.